Presenting a model for safety program performance assessment using grey system theory. Issue 2 (29th July 2014) - Omidvari, Manouchehr; Lashgary, Zeinab
Abstract : Purpose: – The proposed model was capable of being used in both promoting safety performance level and evaluating and ranking safety units. The paper aims to discuss these issues. Design/methodology/approach: – Managers must be able to determine positive impacts of safety programmes on the organisation and level of goal achievement and information access about performance of safety units. Since uncertain judgements of decision makers can be hardly estimated by numerical values, in this paper, based on grey system theory, a method was proposed for evaluating performance of safety units which was done using qualitative criteria of safety performance in an uncertain environment by one of the newest developed theory. This method used concept of grey theory to convert verbal variables into interval grey numbers; in the quantitative method, degree of grey possibility was imported. Findings: – The results showed that the most important performance indicator in the field of safety in inter-urban transportation management included specialized safety training, safety auditing, hazard identification and risk evaluation, employees' health monitoring, solid waste management and management review. Originality/value: – This model could be extended for the whole safety issues and can be used as a simple and efficient method to evaluate performance of safety units in metro company of all the cities in order to determine their weaknesses and introduce the applied control strategies.